Tantangan Pajak Karbon Sebagai Alternatif Kebijakan Transisi Energi Bersih di Indonesia Studi Kasus Industri Otomotif - Wibisono, Adrian Harry; Soepriyanto, Gatot (Owner : Riset dan Jurnal Akuntansi, 2024)
Climate is the average weather where weather is the state of the atmosphere at a given point in time. Climate is defined as the average size and variability of relevant magnitudes of certain variables. Concrete activities in climate change mitigation are reducing and/or preventing greenhouse gas emissions released as a result of human activities. Various activities can be classified as climate change mitigation, including switching to public modes of transportation, using clean renewable energy, Carbon taxes are economically significant for reducing carbon emissions, Carbon Pricing can be used as a tool to determine the external cost of greenhouse gas (GHG) emissions. This study uses signaling theory which was first introduced by Spence in his research entitled job market signaling. The method used by researchers in qualitative descriptive writing with a literature review, the results of the study concluded that France, Sweden, Japan have succeeded in implementing taxes. Even though at the beginning of its implementation there were many objections from various parties and now it has succeeded in having a positive impact on the country's economy, while Indonesia will start implementing a carbon tax from April 2022 on the Coal-Fired Power Plant sector, the carbon tax rate applied is the same as the carbon price. on the carbon market but not less than IDR 30 per kilogram of CO? equivalent.